Sub-Lethal Effects Of Chlorpyrifos On Geno-Neurotoxic Profiles In Freshwater Fish Cyprinus Carpio(L.) (Journal of Pharmaceutical Negative Results, 2023)
Pesticide toxicity is a global concern and chlorpyrifos is one of the most widely used organophosphate agrochemicals,it is frequently detected in surface ground waters of India. Chlorpyrifos(CPF) LC50 – 96 h was calculated as 0.318 mg/l using probit analysis based on LC50 value two sublethal concentrations of 1/5th of LC50 (0.0636 mg/l) and 1/10th of LC50 (0.0318 mg/l) were determined. The influence of CPF on the acetylcholinesterase (AChE) activity and Ach content and the Genotoxicity of Cyprinus carpio was evaluated. Results confer that significant inhibition in the AchE activity in brain tissue resulting in a build-up of Ach at the neuronal synapse resulting in a decrease of cholinergic transmission finally impairs the neurophysiological activity and ultimately result in the death of fish although studies on genotoxic effects of CPF were carried out to examine the prevalence of nuclear abnormalities in freshwater fish Cyprinus carpio using Comet and MN assay in blood erythrocytes and gill cells as percentile tail DNA damage as comets and micronuclei and other nuclear anomalies were scored in erythrocytes of Cyprinus carpio it was found that significant effect was observed for both concentrations and periods of exposure in the treated fishes. The highest DNA damage and increased micronuclei frequency and inhibitory AchE activity in Cyprinus carpio were found to be high on the highest sublethal 1/5th of LC50 followed by Sublethal 1/10th of LC50 concentration. Overall findings imply that AchE and genotoxic biomarkers may be useful diagnostic tools for chlorpyrifos poisoning in biomonitoring programs.